Paganism in Tess of the D’Urbervilles and Jude the Obscure: The Possibility of Faith and Ethics in a Darwinian World - Marie Panter (Cahiers Victoriens et Edouardiens)
This article aims at exploring Hardy’s representation of paganism in Tess of the D’Urbervilles and Jude the Obscure, in the light of Hardy’s Darwinism. While Hardy’s support of paganism has been much debated, the comparison between these two novels shows that everything tends towards an unambiguous praise of paganism, which appears as a possible alternative to Christianity. Hardy reads paganism as a form of pantheism and ethics based on ‘Nature’s Law’, which matches his Darwinian view of nature. Through the pagan theme, his late works show that man may replace God by nature, and that religion, though needing to be deeply renewed, remains necessary for humanity to be able to found an ethical society. By using Darwin, he relates to the early romantic debates with Deism, natural philosophy, and the foundation of republican ethics and politics.